2020
DOI: 10.1017/s1368980020004802
|View full text |Cite
|
Sign up to set email alerts
|

Promoting water consumption among children: a three-arm cluster randomised controlled trial testing a social network intervention

Abstract: Objective: To test the effectiveness of a social network intervention (SNI) to improve children’s healthy drinking behaviours. Design: A three-arm cluster randomised control trial design was used. In the SNI, a subset of children were selected and trained as ‘influence agents’ to promote water consumption–as an alternative to sugar-sweetened beverages (SSB)–among their peers. In the active control condition, all children were simultaneously exposed to the benefits of water consumption. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Given the age of the participants (< 16 years), written informed consent was obtained from a parent or legal guardian as well as the children themselves. Subsequently, the participating schools were randomly assigned to one of the five conditions of the MyMovez project (see [27,31] for a detailed description of the conditions). The current study sample included the five (sub) urban primary schools (i.e., eight classes from grades 4-6) assigned to the condition exposed to the Share H 2 O SNI.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the age of the participants (< 16 years), written informed consent was obtained from a parent or legal guardian as well as the children themselves. Subsequently, the participating schools were randomly assigned to one of the five conditions of the MyMovez project (see [27,31] for a detailed description of the conditions). The current study sample included the five (sub) urban primary schools (i.e., eight classes from grades 4-6) assigned to the condition exposed to the Share H 2 O SNI.…”
Section: Methodsmentioning
confidence: 99%
“…This study was integrated into the Share H 2 O intervention effectiveness study [31], which was part of the second data collection phase of the MyMovez research program (see [40] for a detailed description of the MyMovez program). The study reported on data collected from both the selected influence agents and their peers.…”
Section: Designmentioning
confidence: 99%
See 3 more Smart Citations